2012
DOI: 10.1002/anie.201202702
|View full text |Cite
|
Sign up to set email alerts
|

Controllably Tuning Excited‐State Energy in Ternary Hosts for Ultralow‐Voltage‐Driven Blue Electrophosphorescence

Abstract: Phosphorescent organic light-emitting diodes (PHOLEDs), with 100 % theoretical internal efficiency, are being rapidly developed as a most promising approach to meet the urgent and extensive demand of energy-efficient and portable digital terminals and lighting sources.[1] Thanks to the recent breakthrough of highly efficient blue PHOLEDs [2] and outcoupling technologies, PHOLEDs in full color can already realize extremely high efficiencies that approach those of fluorescent tubes (about 70 Lm W À1 ).[3] Never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
45
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(51 citation statements)
references
References 32 publications
1
45
0
5
Order By: Relevance
“…Using an insulating heteroatom is also an efficient strategy to obtain high E T materials with short π-conjugated pathway. Thus, silicium (silane), [44][45][46][47][48][49] and phosphoryl group (P=O), 40,44,47,[50][51][52][53] may act as an effective breaking point of the π-conjugation between the main core of the molecule and the outer groups linked to the heteroatom (phenyl for example in the case of the efficient electron transporting diphenylphosphine oxide unit). More recently, another efficient molecular design based on a π-conjugation breaking induced by an insulating spiro bridge (Called Donor-Spiro-Acceptor design) has been also successfully introduced in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Using an insulating heteroatom is also an efficient strategy to obtain high E T materials with short π-conjugated pathway. Thus, silicium (silane), [44][45][46][47][48][49] and phosphoryl group (P=O), 40,44,47,[50][51][52][53] may act as an effective breaking point of the π-conjugation between the main core of the molecule and the outer groups linked to the heteroatom (phenyl for example in the case of the efficient electron transporting diphenylphosphine oxide unit). More recently, another efficient molecular design based on a π-conjugation breaking induced by an insulating spiro bridge (Called Donor-Spiro-Acceptor design) has been also successfully introduced in literature.…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, in the last fifteen years, it has been demonstrated that highly efficient blue emission should not be obtained in OLED devices using pure organic singlet exciton emissive layers (EML) but should require more sophisticated EML in which a blue phosphor is doped in an organic host material to harvest both singlet and triplet excitons. 2,[16][17][18][19][20][21][22] Thus, when designing bipolar hosts, one should carefully consider the selection of the donor/acceptor pair and their relative positions within the dye. [14][15][16][17][18] One of the weakest links of this technology remains the design of highly efficient host materials for blue phosphors.…”
mentioning
confidence: 99%
“…[30][31][32][33] This 'steric hindrance' strategy is most of the time performed through the incorporation of a sterically hindered ortho linkage efficiently leading to a π-conjugation restriction. 20 For example, in the 9'triphenylsilanyl-9'H- [9,3',6',9"]ter-carbazole (Sit-Cz), the direct connexion of the silane to a carbazole unit through the nitrogen atom renders this carbazole electro-deficient (HOMO: -5.54 eV, LUMO :-2.3 eV, E T : 3.0 eV). 31 Using an insulating heteroatom is also an efficient strategy to obtain high E T materials with short π-conjugated pathway.…”
mentioning
confidence: 99%
“…The introduction of phosphoryl (P = O)moiety will improve the coordination fields of the ancillary ligand to make a hypsochromic shift. More importantly, P = O is a strong electron-withdrawing group capable of polarizing the molecule, which has been widely used in bipolar host materials and electron transport materials based on its excellent electron transport property52535455565758596061. In our former publications, we also reported some efficient OLEDs with Ir(III) complexes containing the electron transport P = O moiety386263.…”
mentioning
confidence: 91%